Study of Stability, Cytotoxic and Antimicrobial Activity of Chios Mastic Gum Fractions (Neutral, Acidic) after Encapsulation in Liposomes - Olga Gortzi; Magdalini Rovoli; Konstantinos Katsoulis; Konstantia Graikou; Despoina-Aikaterini Karagkini; Dimitrios Stagos; Dimitrios Kouretas; John Tsaknis; Ioanna Chinou (Foods, 2022)
Mastic gum is a resinous sap produced by Pistacia lentiscus growing in the island of Chios (Greece) and has been recognized since Antiquity for its distinctive aroma as well as medical properties (antimicrobial, antioxidant, anti-inflammatory ones). The oral absorption of Chios Mastic gum (an insoluble polymer of poly-β-myrcene is among the most abundant contents) is poor due to its low water-solubility. We report in this study, two different Chios mastic gum extracts, the acidic mastic gum extract—AMGE—and the neutral one—NMGE, both prepared after removal of the contained polymer in order to ameliorate solubility and enhance in vivo activity. Liposomes are presented as a promising delivery system due to their physicochemical and biophysical properties to increase stability and absorption efficiency of the mastic gum extracts within the gastrointestinal (GI) tract. The aim of this study was to evaluate the stability in GI simulated conditions together with cytotoxic and antimicrobial activity of the two extracts (AMGE and NMGE) after encapsulation in a well characterized liposome formulation. Liposomes-AMGE complex showed an improved stability behavior in GI simulated conditions. Both assayed extracts showed significant dose dependent inhibition against the growth of liver cancer HepG2 cells and an interesting antimicrobial activity against several microorganisms. Conclusively, encapsulation could be evaluated as a beneficial procedure for further applications of mastic resin.